THE CORRELATION BETWEEN ADHERENCE TO A LOW-CARBOHYDRATE DIET AND DECREASED BLOOD SUGAR LEVELS IN PATIENTS WITH DIABETES MELLITUS TYPE II AT GRANDMED LUBUK PAKAM HOSPITAL - Reni Novia; Yessy Arisman; Alberta Dame Yanti Zega; Reno Irwanto (JURNAL KESMAS DAN GIZI (JKG), 2023)
Diabetes mellitus is one of the degenerative diseases suffered by many Indonesians who occupy the 6th highest number of sufferers in the world. Indonesia has the number of people with diabetes mellitus in 2017 as many as 10.3 million people and it is predicted that in 2045 this number will increase to 16.7 million people. If this cannot be handled properly, it will cause health problems for sufferers, including increasing the risk of complications. Compliance with a sufferer's diet is an important point to pay attention to in an effort to overcome the problem of diabetes. This compliance plays an important role in influencing the patient's blood glucose levels. Therefore researchers was interested in knowing the correlation between adherence to a low-carbohydrate diet and decreased blood sugar levels in patients with diabetes mellitus type II at Grandmed Lubuk Pakam Hospital. The design of this study was carried out in an observational analytic manner with a cross-sectional method at Grandmed Lubuk Pakam Hospital. The sampling technique was purposive sampling with a total sample of 35 people. The results showed that there was a significant relationship between adherence to a low-carbohydrate diet and decreased blood sugar levels in type II diabetes mellitus patients at Grandmed Lubuk Pakam Hospital. This can be seen from the p-value of 0.04 or p <0.05.